Using literature activities to teach content areas to emergent readers - Donoghue, Mildred R. (Boston : Allyn and Bacon, 2001)
Divided into four sections, text includes more than 500 activities which are planned to meet the development levels, interests, and abilities of children in grades K to 3 who are emergent readers in the beginning literacy program.
Includes bibliographical references and index.
Keywords: Children's literature -- Study and teaching (Early childhood); Reading (Early childhood); Children -- Books and reading; Interdisciplinary approach in education